Relative Efficacy Of Chemical, Bioagent And Organic Ammendments In Managing Root Rot Complex Of Piper Longum (Journal of Plant Disease Sciences, 2020)
Root rot complex induced by Phytopthora, Fusarium, Rhizoctonia, Sclerotium and root knot nematode is major threat in Piper longum growing areas of Vidarbha region of Maharashtra. Experiment was carried out in field to observe the effect of chemical, bio-agent and organic amendments against root rot complex of P. longum. At 15, 30, 45 and 60 DAT minimum disease incidence was recorded in treatment T4: FYM (@ 20t/ha) + Fluopyram 400 SC drenching (@1.2 L/ha) + Neem Cake (@ 500 kg/ha) + T. asperellum (@1 kg/ha) + Copper oxychloride (0.30 %) + Mancozeb (0.25%) i.e. 26.30, 28.02, 30.84 and 30.10 % respectively which was at par with treatment T8: FYM (@ 500kg/ ha) + Fluopyram 400 SC (@1.2 L/ha) + Karanj Cake (@ 500 kg/ha) + T. asperellum (@ 1kg/ha) + Copper oxychloride (0.30%) + Mancozeb (0.25%) i.e. 27.53, 29.04, 31.18 and 31.40% respectively after soil application / drenching. Whereas, maximum disease incidence was originate in control i.e. 32.56 %.
Keywords: Piper longum; Root rot complex; Efficacy; Chemical; Bio-agent and Organic amendments